2020
DOI: 10.7759/cureus.10731
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Presentation of Renal Medullary Carcinoma With Undiagnosed Sickle Cell Trait

Abstract: Renal medullary carcinoma (RMC) is an extremely rare malignancy that has been described in younger male patients of African descent with a history of sickle cell disease or trait. We describe a rather unique case of RMC in an older male patient who initially presented with acute on chronic urinary retention and concern for infection. Further investigation revealed a history of hematuria and long-standing microcytic anemia, and the patient was found to have sickle cell trait (SCT) as part of a workup for malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Renal Medullary Carcinoma (RMC) Renal medullary carcinoma is very rare, representing 0.5-1% of the RCCs [30,47] and it develops more frequently in the 2nd-3rd decades of life, with a higher incidence in Mediterranean and African males [48]. Additionally, it has been observed that patients with sickle cell disease are at increased risk to develop RMC [47][48][49]. This type of carcinoma develops from the distal nephron and is extremely aggressive, with the 3-year survival rate being less than 5% [47,50].…”
Section: Collecting Duct Carcinoma (Cdc)mentioning
confidence: 99%
“…Renal Medullary Carcinoma (RMC) Renal medullary carcinoma is very rare, representing 0.5-1% of the RCCs [30,47] and it develops more frequently in the 2nd-3rd decades of life, with a higher incidence in Mediterranean and African males [48]. Additionally, it has been observed that patients with sickle cell disease are at increased risk to develop RMC [47][48][49]. This type of carcinoma develops from the distal nephron and is extremely aggressive, with the 3-year survival rate being less than 5% [47,50].…”
Section: Collecting Duct Carcinoma (Cdc)mentioning
confidence: 99%